LEGALITAS PENGGUNAAN AUTONOMOUS UNDERWATER VEHICLE DITINJAU DARI HUKUM LAUT INTERNASIONAL - Gian William Sumule (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This thesis aims to research on the legality of the use of Autonomous Underwater Vehicles or AUV according to International Law of the Sea. AUV in general is a small ship compared to ship. AUV is equipped with sophisticated technology where AUV is able to operate autonomously in international seas even without the full supervision of the State. AUV often equated with drones that operate below sea level. The presence of AUV in the international sea law regime is certainly a challenge in regulating the use of AUV. This also impacts on the definition, rights, obligations, and the state's responsibility for the use of AUV according to International Law of the Sea. The technology of AUV has several benefits for a country, such as being able to conduct research in an ocean depth that is not capable of being reached by humans AUV is able to use sensors to look for objects in the sea, as well as to find the debris of aircraft and ships that fall and sink to the sea. This study uses a normative research method which also studies through international treaties that regulate the management and use of marine areas that have been in force.